ROLE OF IMBUING INTERACTIONS ON THE SOCIAL FABRIC OF GOND TRIBE - A COMPREHENSIVE REVIEW - Malik, Garima; Sethi, Sabina (ShodhKosh: Journal of Visual and Performing Arts, 2023)
A tribal community is symbolic of a country’s culture and its values. Comprising 8.6 percent of India’s population, the tribal population is a unique microcosm representative of India’s history, art, culture, rituals, and its people. The Gond tribe is one such Indian tribe, spread across central India whose roots go back far in history to the times when Gondwana existed. Gond dynasty was powerful and culturally significant from the ninth to the sixteenth century. This review paper aims to present a concise compilation of the ethnography of the second-largest tribe residing in India and enumerates their kingdom and victories. It also sheds light on the dispersion of Gond population till present time. The paper also attempts to bring forth the role of their various interactions with other societies and how it influenced their social and cultural practices.